Medicinal plants - Joshi, Shankar Gopal (New Delhi : Oxford & IBH Pub. Co., 2000)
Treatise on Ayurvedic materia medica.
Keywords: Medicinal plants -- India; Materia medica, Vegetable -- India; Medicine, Ayurvedic -- India; Herbs -- Therapeutic use -- India